ORGANIZATIONAL CULTURE, LEADERSHIP, AND ORGANIZATIONAL PERFORMANCE : SYSTEMATIC LITERATURE REVIEW - Fuad Alfaridzi Setiawan; Sopiah Sopiah (Universitas Nusa Cendana, 2026)
This study systematically reviews existing literature to examine how organizational culture and leadership style affect organizational performance. Adopting a descriptive design and qualitative approach, it compiles studies from multiple sources, particularly the Scopus database using the keywords “organizational culture, leadership, and organizational performance” for the period 2019–2024. The synthesis of 17 selected articles shows that a strong organizational culture combined with adaptive, effective, and responsive leadership substantially enhances employee engagement and productivity. The review further indicates that transformational and situational leadership styles are especially effective in aligning employees with organizational cultural values, thereby improving overall performance. Accordingly, the study argues that organizations that invest in a supportive culture and inclusive leadership are more likely to achieve superior performance outcomes, while also providing useful insights for practitioners and leaders in designing strategies to strengthen performance. Keywords: Organizational Culture; Leadership; Organizational Performance